Analysis of Internal Resources as a Determinant of Supply Chain Performance in Coffee Shops in DKI Jakarta - Rahayu Kencana Wati; Wahyuningsih Santosa; Triwulandari Satitidjati Dewayana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of various factors on supply chain performance in coffee shops located in Jakarta. Based on primary data collected from 281 respondents and hypothesis testing results, it was found that E-Procurement, Information Sharing, Stakeholder Collaboration Fluency, Innovation, and E-Payment have a significant effect on supply chain performance. On the other hand, Managerial Competence, Information Quality, Trust, and Organizational Culture showed no significant effect. These findings offer strategic insights for coffee shop businesses to enhance their supply chain efficiency and effectiveness through better use of technology and improved collaboration.